Biochemical changes induced by Coxsackie B4 virus in short-term culture of mouse pancreatic islets. Issue 1 (January 1985) - Szopa, T. M.; Gamble, D. R.; Taylor, K. W.
Abstract : Isolated mouse pancreatic islets were infected in vitro with two strains of Coxsackie B4 virus – a tissue culture – adapted strain and a mouse pancreas-adapted strain. Within 48 h of infection changes had occurred in the biochemical activities of islets infected with the mouse pancreas-adapted strain of virus. Basal insulin release was increased two-fold in these islets, while glucose-induced insulin secretion remained unchanged. Insulin biosynthesis was greatly reduced at a sti, mulatory concentration of glucose (20 raM), thus leading to a reduced insulin content in these islets. These effects are of importance because they demonstrate that certain strains of Coxsackie B4 virus, like encephalo-myocarditis virus, may selectively alter B-cell function in vitro.